2012
DOI: 10.1080/00028487.2012.730106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electrofishing Catch per Unit Effort for Indexing Fish Abundance in Florida Lakes

Abstract: Electrofishing CPUE data are commonly used to index temporal trends in abundance in fish monitoring programs, but the reliability of this index requires the assumption that the fraction of fish stock caught per unit effort (catchability, q) is relatively precise and constant through time. We evaluated how fish species, season, and lake affected electrofishing catchability in Florida lakes using a field study. We used the field study results to simulate how variable electrofishing q affects statistical power an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…For example, Hangsleben et al . () investigated variation in p of largemouth bass ( Micropterus salmoides ) sampled with boat electrofishing in Florida lakes. Their results suggested that p could vary through time and among lakes for unknown reasons between 0.01 and 0.13.…”
Section: Violations Of the Assumption Of Constant Detectionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Hangsleben et al . () investigated variation in p of largemouth bass ( Micropterus salmoides ) sampled with boat electrofishing in Florida lakes. Their results suggested that p could vary through time and among lakes for unknown reasons between 0.01 and 0.13.…”
Section: Violations Of the Assumption Of Constant Detectionmentioning
confidence: 97%
“…Hangsleben, Allen & Gwinn, 2013; see Appendix S1 in Supporting Information for a stylised example of how variable p can impact inference about N). Furthermore, the literature suggests that the probability of spurious conclusions about fish abundance can increase dramatically with only small variations in p (Archaux, Henry & Gimenez, 2012; Hangsleben et al, 2013). For example, Hangsleben et al (2013) investigated variation in p of largemouth bass (Micropterus salmoides) sampled with boat electrofishing in Florida lakes.…”
Section: Violations Of the Assumption Of Constant Detectionmentioning
confidence: 99%
“…Sampling gears with the greatest efficiency (i.e., greatest CPUE or catch per person‐hour) often are selected without consideration of accuracy, precision, or variation in catchability (i.e., fraction of the fish stock collected per unit of effort) related to relative abundance estimates (see Hangsleben et al. ; Gwinn et al. ; and Tyszko et al.…”
mentioning
confidence: 99%
“…Similarly, fish detection increased while abundance decreased with increasing water temperature. This example is not unique; Hangsleben et al (2013) found that annual variability in capture efficiency of boat electrofishing, calculated from the capture of marked and unmarked individuals, coincided with reduced confidence in the utility of catch per unit effort of large-bodied fishes in large lentic systems. Thus, these and other environmental factors affect detection probability of other gear types, seasons, and environments, thus affecting the practitioners' ability to effectively draw inference to habitat relationships and trends in abundance if detection probability is not accounted for in the sampling design.…”
Section: Discussionmentioning
confidence: 99%
“…We based λ on the average estimated species-specific abundance estimates, and variation in p y was simulated as a random draw from a beta distribution and parameterized (a, b) using estimates of species-specific detection probability determined from the Bayesian mixture models. In post-population change years, catch was simulated where site-specific abundance λ was doubled, catch ĩ NBin(2λp y , k) (Hangsleben et al 2013). We compared species-specific estimates among an nual (1 yr) sampling schedules pre-and post-…”
Section: Objective 2: Soak Timementioning
confidence: 99%